Inclusion of discarded banana in sugarcane silage decreases dry matter losses and improves its nutritional value - Jaqueline da P. S. Rodrigues (Universidad de Antioquia, 2019)
Background: Sugarcane silage (SCS) has often been characterized by large dry matter (DM) losses associated with reduction in soluble nutrients and increase in indigestible fiber. Objective: To evaluate the effect of including discarded fruits on the losses and nutritional value in SCS. Methods: A completely randomized design was used with five treatments andfive replications. Silageswere added with 15% (as-fed basis) papaya (Carica papaya) (SP), acerola (Malpighia glabra) (SA), banana (Musa sp.)(SB) or tomato (Solanum lycopersicum) (ST). The control treatment was composed only of SCS. Twenty-five (25-L) plastic buckets were used to make the experimental silos, which were opened on the 90th day after their closure. Data were analyzed by analysis of variance. Results: Gas losses and total DM losses were lower and DM recovery was higher in SB and SA than in the control (p>0.05). However, there was treatment effect for lactic and acetic acids, ammonia nitrogen contents, lactic acid bacteria, and yeasts and mold counts (p<0.05). Conclusion: The inclusion of 15% banana or acerola in SCS decreases losses and increases DM recovery. Furthermore, the inclusion of 15% banana improves the nutritional value of SCS.